Loss of enteric neuronal Ndrg4 promotes colorectal cancer via increased release of Nid1 and Fbln2. (23rd April 2021) - Vaes, Nathalie; Schonkeren, Simone L; Rademakers, Glenn; Holland, Amy M; Koch, Alexander; Gijbels, Marion J; Keulers, Tom G; de Wit, Meike; Moonen, Laura; Van der Meer, Jaleesa R M; van den Boezem, Edith; Wolfs, Tim G A M; et al.
Abstract: The N‐Myc Downstream‐Regulated Gene 4 ( NDRG4 ), a prominent biomarker for colorectal cancer (CRC), is specifically expressed by enteric neurons. Considering that nerves are important members of the tumor microenvironment, we here establish different Ndrg4 knockout ( Ndrg4 −/− ) CRC models and an indirect co‐culture of primary enteric nervous system (ENS) cells and intestinal organoids to identify whether the ENS, via NDRG4, affects intestinal tumorigenesis. Linking immunostainings and gastrointestinal motility (GI) assays, we show that the absence of Ndrg4 does not trigger any functional or morphological GI abnormalities. However, combining in vivo, in vitro, and quantitative proteomics data, we uncover that Ndrg4 knockdown is associated with enlarged intestinal adenoma development and that organoid growth is boosted by the Ndrg4 −/− ENS cell secretome, which is enriched for Nidogen‐1 (Nid1) and Fibulin‐2 (Fbln2). Moreover, NID1 and FBLN2 are expressed in enteric neurons, enhance migration capacities of CRC cells, and are enriched in human CRC secretomes. Hence, we provide evidence that the ENS, via loss of Ndrg4, is involved in colorectal pathogenesis and that ENS‐derived Nidogen‐1 and Fibulin‐2 enhance colorectal carcinogenesis. SYNOPSIS: Loss of enteric neuronal N‐Myc Downstream‐Regulated Gene 4 (Ndrg4) increases the release of the extracellular matrix proteins, Nidogen‐1 and Fibulin‐2, which accelerates intestinal growth in vitro and promotes colorectal cancer progression in vivo . Loss of Ndrg4 is associated with a more aggressive tumor behavior in murine models of colorectal cancer. Medium derived from primary Ndrg4‐/‐ enteric nervous system cells accelerates the growth of murine intestinal organoids. Ndrg4‐/‐ medium is enriched for two extracellular matrix components: Nidogen‐1 and Fibulin‐2. Soluble Nidogen‐1 and Fibulin‐2 stimulate human intestinal organoid proliferation and CRC cell migration in vitro . Abstract : Loss of enteric neuronal N‐Myc Downstream‐Regulated Gene 4 (Ndrg4) increases the release of the extracellular matrix proteins, Nidogen‐1 and Fibulin‐2, which accelerates intestinal growth in vitro and promotes colorectal cancer progression in vivo .